The Effect of Company Size, Profitability and Financial Laverage on Income Smoothing Practices with Good Corporate Governance as Moderating Variables in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange: Pengaruh Ukuran Perusahaan, Profitabilitas Dan Financial Laverage Terhadap Praktik Income Smoothing Dengan Good Corporate Governance Sebagai Variabel Pemoderasi Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa E - Nurani, Etika Vira; Maryanti, Eny (Universitas Muhammadiyah Sidoarjo, 2021)
This research intends to know The Effect Of Company Size, Profitability and Financial Leverage To Income Smoothing Practice With Good Corporate Governance As Moderator Variable For Manufacturing Industry Consumer Goods That Registered At Indonesia Stock Exchange 2016-2018. Earlier research showing different result. Reserch is needed to re-examine the effect of two variables on income smoothing by adding good corporate governance as moderator variable. There are 53 companies in manufacturing industry consumer goods that registered at Indonesia Stock Exchange 2016-2018 research population. based on criteria purposive sampling obtained 31 companies that meet research criteria. This research is using analytical data testing SmartPLS (Partial Least Square). This research resulted in independent variables such as company size affecting income smoothing, while profitability and financial leverage are not affected by income smoothing. Good corporate governanceas a moderating potential variable (Homologiser Moderator) on the effect of company size on income smoothing, profitability on income smoothing, financial leverage on income smoothing.